A Novel Silicon Carbide Nanosheet for High‐Performance Humidity Sensor. Issue 6 (15th January 2018) - Sun, Lian; Wang, Bing; Wang, Yingde
Abstract: Two‐dimensional (2D) structure is a good candidate for fabricating humidity sensors due to its advantages including high surface/volume ratio, abundant active sites, and fast carrier motion rate. Here, an impedance‐type nonoxide humidity sensor based on silicon carbide nanosheets (SiC NSs) is prepared via carbothermal reduction between graphene oxide and silicon powder. The final product, with a high surface area of 90.1 m 2 g −1, contains SiC with a thin oxide layer on the surface and some remained reduced graphene oxide. The synthesized SiC NSs exhibit excellent sensing properties such as a high sensitivity to water in ambient atmosphere (16991.1 at 95% relative humidity (RH)), a wide range of RH response (11–95%), short response time (3 s) and recovery time (3 s), and good linear response toward humidity, which are more excellent than the commercial SiC nanowires and most of the nanostructure humidity sensors in literature. The good humidity sensing performance of this sample can be contributed to the advantage of nanosheet structure, the fast electron transfer rate in the SiC semiconductor, and the donor effect of electrons. This report provides a technical guidance on the designing of novel 2D structure nonoxide humidity sensors. Abstract : A novel silicon carbide nanosheet is prepared and shows excellent humidity sensing properties, significantly better than one‐dimensional (1D) SiC nanostructures as well as other nanomaterial‐based humidity sensors.